Student's perception of utility and application of skills taught during the foundation course at a medical college in central Uttar Pradesh, India - Vibha Gangwar; Manish Kumar Singh; Amrita Lumbani (Journal of Family Medicine and Primary Care, 2022)
Context: “Foundation course” is an orientation program for MBBS students at time of entry into medical college. Aims: To study the MBBS student's perception of relevance and level of confidence in application of skills acquired in foundation course and its predictors. Settings and Design: A cross sectional study was done among second year MBBS students at a medical college in central Uttar Pradesh, India. Methods and Material: Data was collected online using a Google form over 1 month. About 97 (out of 200) students participated in the study. Final analysis was done for 94 responses. Statistical Analysis Used: Chi Square test for proportions. Results: Overall 83% students found foundation course to be relevant. Sessions on professional development & ethics (94.6%), biomedical waste management (94.6%), social responsibility of doctors (91.5%), communication skill (93.6%), role and responsibilities of Indian Medical Graduate (93.6%), universal precautions (91.5%), immunisation (91.5%) and assessing E –resource (90.4%) were rated as most relevant. Computer skills and sports/extra-curricular activities were perceived as non-relevant by 29% and 16% students respectively. Overall 61% students were confident about application of knowledge/skills acquired in the foundation course. A significant difference was observed for gender and medium of education with regards to level of confidence in application of certain skills/knowledge. Conclusions: Foundation course was perceived as relevant by most students. However, level of confidence with regards to application of skills/knowledge was found to be variable with significant difference for some variables.